Hypertrophic Cardiomyopathy. (March 2015) - Hensley, Nadia; Dietrich, Jennifer; Nyhan, Daniel; Mitter, Nanhi; Yee, May-Sann; Brady, MaryBeth
<x xml:space="preserve">Abstract</x> Hypertrophic cardiomyopathy (HCM) is a relatively common disorder that anesthesiologists encounter among patients in the perioperative period. Fifty years ago, HCM was thought to be an obscure disease. Today, however, our understanding and ability to diagnose patients with HCM have improved dramatically. Patients with HCM have genotypic and phenotypic variability. Indeed, a subgroup of these patients exhibits the HCM genotype but not the phenotype (left ventricular hypertrophy). There are a number of treatment modalities for these patients, including pharmacotherapy to control symptoms, implantable cardiac defibrillators to manage malignant arrhythmias, and surgical myectomy and septal ablation to decrease the left ventricular outflow obstruction. Accurate diagnosis is vital for the perioperative management of these patients. Diagnosis is most often made using echocardiographic assessment of left ventricular hypertrophy, left ventricular outflow tract gradients, systolic and diastolic function, and mitral valve anatomy and function. Cardiac magnetic resonance imaging also has a diagnostic role by determining the extent and location of left ventricular hypertrophy and the anatomic abnormalities of the mitral valve and papillary muscles. In this review on hypertrophic cardiomyopathy for the noncardiac anesthesiologist, we discuss the clinical presentation and genetic mutations associated with HCM, the critical role of echocardiography in the diagnosis and the assessment of surgical interventions, and the perioperative management of patients with HCM undergoing noncardiac surgery and management of the parturient with HCM.